Contribuição de quintais agroflorestais para a segurança alimentar de agricultores familiares no Baixo Irituia, Nordeste Paraense - MIRANDA, Silviane Batista (Universidade Federal do Pará, 2021)
The yards are agroecosystems agroforestry located near residences, composed of a variety of plant species (food, medicinal, ornamental and timber) and small animals, providing products that contribute to a diverse and healthy diet. The purpose of the study was to evaluate the contribution of agroforestry gardens for food security in small family farmers in the Lower Irituia, Northeast Pará. It starts with the hypothesis that families with agroforestry gardens have access to a greater quantity and quality of perishable food and a lower consumption of processed products compared to those who do not have backyards agroforestry. The study was conducted in the communities of Ajara, Araraquara, and Santa Terezinha Puraquequara family farmers in 30 of which agroforestry gardens have 18 and 12 do not. Through the techniques of structured interviews and semi-structured, guided tours, direct observation and recall 24 hours were carried out a survey of the species (plant and animal) 18 yards in agroforestry and verification of the food consumed by 30 households interviewed, both those produced in the backyards agroforestry or not, and those of industrial origin. We studied 18 yards agroforestry rose 125 species of plants and five animal species. Of the 130 plant and animal species, 70 are food plants (of which 44 are fruit, 21 vegetable crops and 5 white tillage (such as cassava, rice and corn), 31 are medicinal, are 17 timber, 7 and 5 are ornamental food and animals. Of the 70 food species, 94% being consumed by the families interviewed, especially the fruit (59%), followed by vegetable crops (30% of total) and the white farming (11% of total). The species fruit is consumed in the form of juice (especially after meals) or fresh (for the occasional picnic). Banana, cashew, guava, cupuaçu, pineapple, lemon and orange are the most consumed fruit in the gardens as cashew and banana agroforestry agroforestry gardens without spaces. The species most commonly found and consumed in both the chicken yard, which is designed for self- consumption and sale. agroforestry gardens Farmers have access to a better nutritional status by consuming greater quantities and variety of food from the gardens, especially fruits, rich in vitamins and minerals. With respect to the consumption of foods were collected from farmers in agroforestry gardens without spaces while among the 17 items with 15 items agroforestry gardens, and food most consumed by two groups: rice, coffee, oil and sugar. industrialized products such as bologna, artificial juice and chicken farm were consumed in higher percentages by farmers in agroforestry gardens without spaces. By applying the Student test showed a difference statistically significant in the mean amount of food consumed (in backyards and industrial) by two groups of farmers in the two periods of the year (rainy and dry), confirming the hypothesis of the research. Backyards agroforestry is therefore important to introduce changes in diet, they contribute in the diversification and complementary feeding.